(-2 1/8)×(-1 29/51)+(-1 23/42)×3 1/3-(-4 2/3)×6 Умоляю вас у нас СОЧ не пишите фигню
УМОЛЯЮ ВАС ОЧЕНЬ НУЖНО​

rsobal45gmailcom rsobal45gmailcom    3   25.12.2020 07:26    0

Ответы
Адай111111 Адай111111  25.12.2020 07:30

(-2 1/8) * (-1 29/51) + (-1 23/42) * 3 1/13 - (-4 2/3) * 6 = 26 целых 4/7

1) (-2 1/8) * (-1 29/51) = 17/8 * 80/51 = (1*10)/(1*3) = 10/3 = 3 1/3

2) (-1 23/42) * 3 1/13 = (-65/42) * 40/13 = -(5*20)/(21*1) = -100/21 = -4 16/21

3) (-4 2/3) * 6 = (-14/3) * 6 = -14 * 2 = -28

4) 3 1/3 + (-4 16/21) = -(4 16/21 - 3 1/3) = -(4 16/21 - 3 7/21) = -1 9/21 = -1 3/7

5) -1 3/7 - (-28) = -1 3/7 + 28 = 28 - 1 3/7 = 27 7/7 - 1 3/7 = 26 4/7

Пошаговое объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика